<sklopený text>In silico modelling of the effect of bacterial DNA fragmentation on gene counts using digital droplet PCR - Vranjes, Sebastian (Jihočeská univerzita, 2022)
The aim of this study is to establish a correction factor for ddPCR, accounting for instances of the target sequence's occurrences being miscounted due to endpoint detection limitations.
<sklopený text>In silico modelling of the effect of bacterial DNA fragmentation on gene counts using digital droplet PCR
Keywords: ddPCR; DNA Fragmentation; 16S rRNA; end-point detection; Python; correction factor; ddPCR; DNA Fragmentation; 16S rRNA; end-point detection; Python; correction factor